Investigation the Role of IL-17 rs2275913 Gene Polymorphism with the Risk of Osteoporosis in a Sample of Iraqi Pre and Postmenopausal Women - Asmaa Mahmoud Salman; Da'ad A. Hussain (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: This study aimed to investigate the relationship between the genetic polymorphism and allelesfrequencies of IL-17 rs2275913 G/A with the risk of low bone mineral density (osteoporosis and osteopenia).Furthermore studying the relation between some immunological and biochemical parameters with thisdisease in a sample of Iraqi pre and postmenopausal women. Methodology: In this study, we investigatedabout the IL-17 rs2275913 G/A polymorphisms and the risk of low bone mineral density (BMD) among30 patients with osteopenia, 30 patients with osteoporosis and 30 healthy controls. Serum IL-17 level andits correlation with the IL-17 rs2275913 G/A genotypes were analyzed. The study was carried out fromNovember 2020- January 2021 in Baghdad Teaching Hospital/ Bone density examination unit/ in Baghdad-Iraq. Conclusion: It is concluded that the IL-17 rs2275913 G/A genotype was not associated with increasedrisk for development of low (BMD) in Iraqi pre and postmenopausal women. Recommendation: Based onstudy conclusion, during menopause, it is important for women to have a DEXA scan to detect low BMDand receive appropriate care to prevent degradation of the micro-architecture of bone tissue, which increasesthe risk of bone fractures.